Inkjet‐Printed Mesoporous TiO2 and Perovskite Layers for High Efficiency Perovskite Solar Cells. Issue 2 (28th December 2018) - Huckaba, Aron J.; Lee, Yonghui; Xia, Rui; Paek, Sanghyun; Bassetto, Victor Costa; Oveisi, Emad; Lesch, Andreas; Kinge, Sachin; Dyson, Paul J.; Girault, Hubert; Nazeeruddin, Mohammad Khaja
Abstract: Perovskite solar cells with mesoporous TiO2 electron transport layers have previously reached >22 % efficiency at the laboratory scale (<1 cm 2 ), however, these layers are fabricated using spin‐coating, which is not conducive to large‐scale or high throughput fabrication. This report describes the inkjet printing of open‐pore mesoporous TiO2 thin films, perovskite thin films, and the fabrication of highly efficient perovskite solar cells using these films. Ink formulation and characterization studies, inkjet deposition optimization trials, film characterization, and comparison to spin‐coated layers are described. The printed TiO2 films exhibited an open‐pore morphology and homogeneous surface coverage in films ranging from 1 mm 2 to >10 cm 2 . Perovskite solar cells with printed and pristine (un‐doped) inkjet‐printed TiO2 layers yielded efficiencies of 18.29 %, which were found to outperform cells made with spin‐coated and pristine TiO2 layers (16.91 %). When a quadruple‐cation perovskite absorber containing Cs, formamidinium, methylammonium, and guanidinium was deposited by inkjet‐printing onto the inkjet‐printed TiO2 layer, nearly 12 % average efficiency was reached, with the champion cell reaching 14.11 %. This absorber exhibited higher efficiency and stability than did inkjet‐printed MAPbI3 films deposited on the inkjet‐printed TiO2 film. Abstract : This report describes the inkjet printing of open‐pore mesoporous TiO2 thin films, perovskite thin films, and the fabrication of highly efficient perovskite solar cells using these films. Devices incorporating an inkjt‐printed TiO2 layer outperformed devices with spin‐coated devices.